Constraints and Freedom of Action: a fitness trade-off - Massimo Ricottilli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
This paper attempts to discuss the role of constraints in network formation and in the exploration process of complex spaces of fitness possiblities. It is held that similarities appear in both social and biological systems. The paper further argues that constraints are instrumental in setting a fitness trade-off between specialised and across-the-board searching.
Keywords: 330